Early and widespread cerebellar engagement during hippocampal seizures and interictal discharges - M.L. Streng; B.W. Kottke; E.M. Wasserman; L. Zecker; L. Luong; S. Kodandaramaiah; T.J. Ebner; E. Krook-Magnuson (Neurobiology of Disease, 2025)
Despite research illustrating the cerebellum may be a critical circuit element in processes beyond motor control, and growing evidence for a role of the cerebellum in a range of neurological disorders, including the epilepsies, remarkably little is known about cerebellar changes during seizures. We therefore implemented a novel method for repeated widefield calcium imaging of the cerebellum in awake, chronically epileptic mice. We found widespread changes in cerebellar Purkinje cell activity during temporal lobe seizures. Changes were noted in the anterior and posterior cerebellum (lobules IV-VII), along the midline (vermis), and both ipsilaterally and contralaterally (in the simplex and Crus I) to the seizure focus. This was true for both overtly behavioral seizures and for hippocampal seizures that remained electrographic only – arguing against cerebellar modulation simply reflecting motor components. Moreover, even brief interictal spikes produced widespread alterations in cerebellar activity. Perhaps most remarkably, changes in the cerebellum also occurred prior to any noticeable change in the hippocampal electrographic recordings. Together these results underscore the relevance of the cerebellum with respect to seizure networks, warranting a more consistent consideration of the cerebellum in epilepsy.